2009
DOI: 10.1248/bpb.32.1710
|View full text |Cite
|
Sign up to set email alerts
|

Ginsenoside Rh2 Ameliorates Scopolamine-Induced Learning Deficit in Mice

Abstract: To understand memory-enhancing effect of red ginseng biotransformed by Bifidobacterium longum H-1 (RGB), which more potently improved scopolamine-induced learning deficit than red ginseng in the preliminary experiment, its main constituents, ginsenosides Rb1, Rg3 and Rh2, were isolated and their memory-enhancing effects investigated in scopolamine-treated mice by using passive avoidance and Y-maze tests. Among them, ginsenoside Rh2 most potently reversed memory impairment caused by scopolamine. Ginsenoside Rh2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
36
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 31 publications
2
36
0
Order By: Relevance
“…[8][9][10] 20(S)-Ginsenoside Rh2 (GRh2), with a dammarane skeleton, belongs to the protopanaxadiol family and has drawn attention in chemopreventive research. [11][12][13] Recently, researchers have found that 20(S)-GRh2 exhibits anticancer effects and could inhibit growth of several cancer cell lines and induce apoptosis in mammalian tumor cells. [14][15][16] However, the details of the signal transduction cascade involved in 20(S)-GRh2-induced death in Reh cells remaine unclear.…”
mentioning
confidence: 99%
“…[8][9][10] 20(S)-Ginsenoside Rh2 (GRh2), with a dammarane skeleton, belongs to the protopanaxadiol family and has drawn attention in chemopreventive research. [11][12][13] Recently, researchers have found that 20(S)-GRh2 exhibits anticancer effects and could inhibit growth of several cancer cell lines and induce apoptosis in mammalian tumor cells. [14][15][16] However, the details of the signal transduction cascade involved in 20(S)-GRh2-induced death in Reh cells remaine unclear.…”
mentioning
confidence: 99%
“…25 Further, ginsenoside Rh 2 ameliorates Scopolamineinduced learning deficit in mice. 26 Because there is little evidence in the literature for improvement in memory and learning by ginsenoside Rh 2 , the present study provided reasonable mechanism for ginsenoside Rh 2 -mediated regulation of memory and learning in mice.…”
mentioning
confidence: 52%
“…The nootropic signaling pathway has also been assessed in normal rats, and the Rg1-induced signaling pathway is similar to memory formation that occurs in mammals, suggesting that Rg1 may potentially increase intellectual capacity in normal people [24]. Ginsenoside Rh2 recovers the scopolamine-induced reduction in long-term potentiation (LTP) in the hippocampal CA1 area [25]. Rb1 enhances the stimulatory effect of neurite outgrowth [26], promotes neurotransmitter release by modulating phosphorylation of synapsins through a cAMP-dependent protein kinase pathway [27], upregulates cell genesis in the dentate gyrus (DG) and CA3 hippocampal subregions [28].…”
Section: Panax Ginsengmentioning
confidence: 99%
“…Related to the memory deficit-protecting effects of ginsenosides, ginsenoside Rg3 and ginsenoside Rg5/Rk1 mixture (1:1, w/w), isolated from heat-processed ginseng, show a memory enhancing effect in scopolamine-treated mice [32]. Ginsenoside Rg3 isolated from red ginseng and its metabolite ginsenoside Rh2, as well as ginsenoside Rg1, also protected against scopolamine-induced memory deficit in mice [25,33]. However, when ginsenoside Rg5 was incubated with human feces, it was metabolized to ginsenoside Rh3 [32].…”
Section: Panax Ginsengmentioning
confidence: 99%
See 1 more Smart Citation